Karakteristik Tegangan Tembus AC Pada Material Isolasi Padat Campuran Resin Dengan Alumina (AL2O3) - Abdul Rasyid; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Resin is the polymer material that can be used as high voltage insulators that have high volume resistivity, lighter, high insulation strength and good mechanical strength.Alumina (Al2O3) is one of oxide ceramic that is widely use in the electronic and mechanical material. This research proposes the breakdown voltage test on alumina filler with varies of weight i.e 0.1gr, 0.2gr, 0.3gr, 0.4gr, 0.5gr, 0.6gr, 0.7gr, 0.8gr, 0.9gr, 1gr, 1.1gr, 1.2gr , 1.3gr, 1.4gr, 1.5gr, 1.6gr, 1.7gr, 1.8gr, 1.9gr and 2gr, respectively. The shape of dimension sample is presented in 2x2x2cm with two electrode (needle and plane electrode) inside alumina and resin 0,5cm gap.Keywords –resin, alumina (AL2O3), discharge current, breakdown voltage